Daily field checking list by Walter Rosene, April 18, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Ledges State Park and Little Wall Lake by Walter Rosene, April 18, 1937. Also notes he took movies of several types of flowers and a pair of Grebes diving. Plustek--flatbed